2021
DOI: 10.1007/s12070-021-02758-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tracheostomy in COVID-19 Patients: A Single Centre Experience

Abstract: The rapid emergence of COVID-19 has led to increase in the number of patients requiring prolonged ventilation and tracheostomy. Though global guidelines are evolving, there is a paucity of literature about optimal timing and outcome after tracheostomy in COVID-19 patients. We set out to assess the clinical characteristics and outcome of COVID-19 patients who underwent tracheostomy.This single-center, prospective observational cohort study analyzed all the consecutive tracheostomy performed on COVID-19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Figure 1 shows the flow diagram of study selection process. A total of 14 studies [21][22][23][31][32][33][34][35][36][37][38][39][40][41] 8 retrospectively conducted; 8 single-center studies and 6 multicenter studies) from Asia, Europe and America, involving 2371 tracheostomized COVID-19 patients (938 in the ET group vs. 1433 in the LT group), were incorporated in our meta-analysis. The majority of the studies were conducted during the first wave of COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the flow diagram of study selection process. A total of 14 studies [21][22][23][31][32][33][34][35][36][37][38][39][40][41] 8 retrospectively conducted; 8 single-center studies and 6 multicenter studies) from Asia, Europe and America, involving 2371 tracheostomized COVID-19 patients (938 in the ET group vs. 1433 in the LT group), were incorporated in our meta-analysis. The majority of the studies were conducted during the first wave of COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the mean period of intubation before a tracheostomy was 9.97 ± 2.72 days. A recent study by Chandran A et al reported a mean of 10.27 days from intubation to tracheostomy [ 20 ]. Another study by Chao TN et al reported an average time of intubation before a tracheostomy of 19.7 ± 6.9 days, with a range of 8–42 days [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality among COVID-19 patients who underwent tracheostomy in previous published studies ranged from 7% to 41% [ 9 , 21 ]. Moreover, a study by Chandran A et al had an overall 30-day mortality of 66.66% [ 20 ]. In this study, the overall 30-day mortality rate was 38.4%, which is an acceptable rate in comparison to the previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations